Pengaruh Pembelajaran dengan Menggunakan Modul Berbantuan Simulasi terhadap Peningkatan Penguasaan Konsep Mahasiswa Calon Guru Fisika pada Materi Gelombang Mekanik - Rohmawati, Widya; Sutopo, Sutopo; Taufiq, Ahmad; Manaf, Zuerdiana Binti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study aims to determine the effectiveness of simulation-assisted teaching materials in increasing conceptual understanding of prospective physics teacher students about mechanical waves. Research method is a one-group pretest-posttest design with subjects consisted of 25 physics education undergraduate students at Universitas Negeri Malang. Research instrument is a conceptual understanding test item of mechanical waves. The results showed that the acquisition of an increase in learning outcomes through the calculation of the normalized average gain is 0.77 was included in the "high" category so that the use of simulation-assisted teaching materials effective in improving students' conceptual understanding. Similar learning can be applied to other physics materials, especially for abstract material characteristics.